Mechanisms of germ cell survival and plasticity in Caenorhabditis elegans. (31st October 2022) - Cao, Wei; Pocock, Roger
Abstract : Animals constantly encounter environmental and physiological stressors that threaten survival and fertility. Somatic stress responses and germ cell arrest/repair mechanisms are employed to withstand such challenges. The Caenorhabditis elegans germline combats stress by initiating mitotic germ cell quiescence to preserve genome integrity, and by removing meiotic germ cells to prevent inheritance of damaged DNA or to tolerate lack of germline nutrient supply. Here, we review examples of germline recovery from distinct stressors — acute starvation and defective splicing — where quiescent mitotic germ cells resume proliferation to repopulate a germ line following apoptotic removal of meiotic germ cells. These protective mechanisms reveal the plastic nature of germline stem cells.